Breath volatile organic compounds of lung transplant recipients with and without chronic lung allograft dysfunction. (20th June 2018) - Küppers, L; Holz, O; Schuchardt, S; Gottlieb, J; Fuge, J; Greer, M; Hohlfeld, J M
Abstract: Introduction. Chronic lung allograft dysfunction with its clinical correlative of bronchiolitis obliterans syndrome (BOS) remains the major limiting factor for long-term graft survival. Currently there are no established methods for the early diagnosis or prediction of BOS. To assess the feasibility of breath collection as a non-invasive tool and the potential of breath volatile organic compounds (VOC) for the early detection of BOS, we compared the breath VOC composition between transplant patients without and different stages of BOS. Methods. 75 outpatients (25 BOS stage 0, 25 BOS stage 1 + 2, 25 BOS stage 3) after bilateral lung transplantation were included. Exclusion criteria were active smoking, oxygen therapy and acute infection. Patients inhaled room air through a VOC and sterile filter and exhaled into an aluminum reservoir tube. Breath was loaded directly onto Tenax ® TA adsorption tubes and was subsequently analyzed by gas-chromatography/mass-spectrometry . Results. The three groups were age and gender matched, but differed with respect to time since transplantation, the spectrum of underlying disease, and treatment regimes. Relative to patients without BOS, BOS stage 3 patients showed a larger number of different VOCs, and more pronounced differences in the level of VOCs as compared to BOS stage 1 + 2 patients. Logistic regression analysis found no differences between controls and BOS 1 + 2, but four VOCs (heptane, isopropyl-myristate, ethyl-acetate, ionone) with a significant contribution to the discrimination between controls and BOS stage 3. A combination of these four VOCs separated these groups with an area under the curve of 0.87. Conclusion. Breath sample collection using our reservoir sampler in the clinical environment was feasible. Our results suggest that breath VOCs can discriminate severe BOS. However, convincing evidence for VOCs with a potential to detect early onset BOS is lacking.